Alpe d'Huez: Direct quanitification of the up-hill cycling power output relationship - Martin, D.; Ebert, T.; Quod, M.; Lee, H.; Stephens, B.; Schumacher, Y. O. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Power output during uphill cycling can be estimated based on 1) the heart rate - power output relationship or 2) the mathematical relationship between cycling speed, power output and estimates of resistive forces. The purpose of this study was to explore the utility of directly quantifying the power output - cycling speed relationship for a hillclimb of interest. Validation Trials - Nine male road cyclists who were members of the AIS-SA.com continental cycling team cycled up a 2.4km, 8.9% climb (Black MTN) twice per day for 1-4 days. Dynamically calibrated SRM power meters (4 sg version) were used quantify power and speed during hill climbs (1Hz) and a time trial format was used for all climbs. A complete data set was collected for 56 climbs. The relationship between average power-to-mass and average speed for efforts <18kph (n=42) was established using linear regression analysis. This regression equation was used to estimate the average power output (W.kg-1) associated with faster climbs - 18.0-19.5 kph (n=14). Alpe d`Huez Trials - Using a similar approach, SRM power-speed data were collected from cyclists and triathletes (n=7) who were either training or competing on Alpe d`Huez (13.8km, 8.1%). A powerspeed regression was calculated for the first two hill-climb split times recorded during the 2004 Tour de France (bottom 7.45km, 9.0%; top 3.5km, 8.3%). The initial and final segments of the time trial were not evaluated because cycling speeds >30kph would introduce assumptions associated with aerodynamic drag. During Black MTN trials average speed ranged from (13.2-17.9 kph) and corresponding power ranged from (4.1-5.9 W.kg-1). Average power-to-mass could be predicted by average climbing speed; Power(W.kg-1) = .3411*Speed(kph) - .229; R2=.93; P<.001; N=42. This equation predicted average W.kg-1 for climbing speeds 18.0-19.5kph within .15 W.kg-1 in 14 validation cases (predicted vs estimated was < .1 W.kg-1 in 11/14 cases) confirming good predictability beyond the data set when climbing speeds were <25kph. For the Alpe d`Huez trials average speed was between 11-18 kph and average power was between 2.8- 5.2 W.kg-1. The two equations for predicting hill climbing power were - Bottom; Power(W.kg-1) = .3303*Speed(kph) - .9184; R2=.93; P<.001; N=13 and Top; Power(W.kg-1) = .3101*Speed(kph) - .8136; R2=.96; P<.001; N=11. Overall, it took Armstrong 31:36 to climb 11 km at 8.8% which equates to an average cycling velocity of 20.8kph. This velocity would require 5.85W.kg-1 total mass or 6.5W.kg-1 body mass. Assuming Armstrong`s 2004 time trial up Alpe d`Huez was well paced and that his total mass was 79kg, then his time of 39min and 41sec for the 15.5km TT would have required an average power output of 460W. Cycling power meters can be used to establish the power-to-mass speed relationship for climbs with an acceptable degree of accuracy.